Research on Energy Management Strategy for Mining Trucks with Methanol Range-Extender and Hybrid Energy Storage System - Yafeng Ren; Yusheng Luo; Wenwen Lu; Jiaxin Qin (Energies)
In the field of mining transportation, methanol range-extended powertrain systems are emerging as the preferred solution to address heavy-duty transport challenges in mining areas, leveraging their low-carbon emissions and long-range endurance. However, conventional energy storage technologies face trade-offs between energy density, power density, and cycle life: lithium-ion batteries (Li-ion) have a high energy density but short cycle life, while supercapacitors (SCs) have a high power density and long cycle life but low energy density. To address these limitations, a hybrid energy storage system (HESS) combining Li-ion and supercapacitors (SCs) is proposed as the energy storage unit for the methanol range-extended mining truck (MRMT) in this study. Firstly, the power architecture of MRMT with HESS is designed. Then, the range-extender, Li-ion battery, and SCs are matched and selected based on the operating conditions of the mining truck. Finally, a whole vehicle energy management strategy is developed, and the vehicle power system performance is simulated by combining MATLAB/Simulink (R2022a) with AVL-Cruise (R2019.2). Comparison with conventional single Li-ion range-extender system reveals that the MRMT with HESS reduces methanol consumption by 6.4% and extends the cycle life of Li-ion by 353.4%. This study provides a technological path for the green transformation of mine transportation that is both economical and sustainable.